Conservation Laws in Thomas's Model of Ion Exchange in a Heterogeneous Solution - Ibragimov, N.H.; Khamitova, Raisa (Discontinuity, Nonlinearity, and Complexity, 2026)
Physically significant question on calculation of conservation laws of the Thomas equation is investigated. It is demonstrated that the Thomas equation is nonlinearly self-adjoint. Using this property and applying the theorem on nonlocal conservation laws the infinite set of conservation laws corresponding to the symmetries of the Thomas equation is computed. It is shown that the Noether theorem provides only one of these conservation laws.